(untitled) (Brazilian Journal of Behavioral and Cognitive Therapy, 2016)
In the reprint in this special issue of my 1974 paper, Are behavioral principles for revolutionaries?, I make the point that I remake in the article below: the definition of problem behavior and the contingencies affecting its change are affected by the extent to which the individuals whose behavior is being targeted participate in the definition. Contingencies designed to impact human behavior can have deleterious effects if the imposition of these contingencies is on those without power or choice. When those in power enlist the expertise of behaviorists to change the behavior of those without power, our science tells us that the results will not be what some may expect. I conclude with lessons from the misapplications of behavior analysis in stratified power systems that should affect our professional behavior to diminish the likelihood of additional misapplications of our science.